Auto-Bdcklund transformation for some nonlinear partial differential equation - Inan, Ibrahim E.; Ugurlu, Yavuz; Bulut, Hasan (Elsevier Gmbh, 2016)
In this paper, we apply auto-Backlund transformation for Sharma-Tasso-Olver (STO) equation and fourth order equation of the Burgers hierarchy. Auto-Backlund transformation was developed as a direct and simple method to obtain solutions of nonlinear partial differential equations by Fan. We obtain solitary wave solutions of these equations. The numerical simulations are added to these obtained solutions (C) 2016 Elsevier GmbH. All rights reserved.
Keywords: Auto-Backlund transformation; STO equation; Fourth order equation of the Burgers hierarchy; Solitary wave solution; Kink solution; Singular solution